EP.WE.434Impact Of COVID-19 Pandemic On Approach To Patients With Suspected Appendicitis Pre-Covid V/S Early Covid V/S Late Covid. (28th October 2021) - Alhabsha, Osama; Kudchadkar, Shantata J; Sinclair, Elizabeth; Sagar, Jayesh
Abstract: Introduction: COVID-19 brought concerns of increased perioperative mortality and spread of infection during aerosol generating procedures. As a consequence, intercollegiate guidelines recommended Computed Tomography to confirm the diagnosis of acute appendicitis and open surgical approach to minimize aerosol generation. Aims: To identify the impact of COVID-19 on the diagnostic and management approach for patients with acute appendicitis. Method: A single-centre, retrospective study. Data of patients suspected/confirmed, clinically/radiologically with acute appendicitis was collected over 3 periods of 6.4 weeks. Pre-COVID (11/02/2020 – 22/03/2020), Early COVID (25/03/2020 – 10/05/2020) and Late COVID (23/10/2020 – 06/12/2020), number of patients is 44, 22 and 30, respectively. Outcomes included patient demographics, COVID status, management plan, surgical approach (open v/s laparoscopic), imaging modality, admission to critical care, 30-day complication, mortality and length of stay. Results: During late COVID, number of patients with acute appendicitis slightly increased as compared to initial phase. Interestingly, number of males were consistent throughout all 3 phases. Only 10% presented with perforation during late versus 50% in Early COVID phase. Imaging decreased significantly during late (33.3%), as compared to early phase (72.7%). Open approach was performed in only 1/30 in late, versus 20/21 in early group. There was no 30-day mortality in all 3 groups. Conclusion: COVID-19 disrupted the usual surgical management plan of acute appendicitis in UK, during initial phase of lockdown. With the use of appropriate strategies and adherence to latest national guidelines, we were better prepared during the second lockdown. Construction of pathways for such pandemic events is helpful.